Effect of Sperm Cryopreservation on miRNA Expression and Early Embryonic Development - Xu, Xiaoyu; Li, Wanqiong; Zhang, Lina; Ji, Yazhong; Qin, Jiaying; Wang, Lu; Wang, Mingwen; Qi, Lingbin; Xue, Jinfeng; Lv, Bo; Zhang, Xunyi; Xue, Zhigang (Frontiers in Cell and Developmental Biology, 2021)
Although sperm preservation is the most extensive way for personal fertility preservation, the effects and embryonic development potential of sperm cryopreservation need further investigation. The purpose of this study was to identify key microRNAs (miRNAs) expression of cryopreserved sperm that determine the potential embryonic development by miRNA sequencing. Moreover, the embryonic developmental potential of sperm cryopreserved were estimated in assisted reproductive technologies (ARTs), key miRNAs and target genes were validated in sperm and subsequently embryo by quantitative real-time PCR (qRT-PCR). The clinic data of embryonic development which used cryopreserved sperm indicated the significant decrease of fertilization rate in both in-vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cases, as well as the reduction of blastocyst formation rate in ICSI cases, while the significant increase of blocked embryo ratio of Day1, Day2, Day3.5 embryos were observed when used the frozen-thawed sperm compared with fresh sperm, suggesting the potential negative effects of sperm cryopreservation on embryonic development. Between frozen-thawed and fresh sperm in human and mouse, 21 and 95 differentially expressed miRNAs (DEmiRs) were detected, respectively. miR-148b-3p were validated that downregulation in both human and mouse frozen-thawed sperm, and also decreased in subsequently embryo after fertilization using cryopreserved sperm. Target genes of miR-148b-3p, including Pten, Jmy, Bbc3 and Cdk19 were also identified in mouse embryo. In addition, common character of cryopreservation on mouse oocyte compared with sperm were also detected, downregulation of miR-148b-3p were also confirmed in cryopreserved oocyte. In sum, our study suggested that cryopreservation could change the expression of miRNAs in both sperm and oocyte, miR-148b-3p and targeted Pten in sperm cryopreservation further affected the fertilization and development of embryo.